2024
DOI: 10.1002/em.22584
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenotoxicity effects in addicts with multidrug consumption

Ana Elizabeth González‐Santiago,
Alejandro Salvador Gómez‐Cabrera,
Raúl Cuauhtémoc Baptista‐Rosas
et al.

Abstract: Drug abuse is considered a global health problem with serious social impact. In recent decades, changes in drug consumption patterns have shown a clear rising trend in the use of multiple drugs. Although the buccal micronucleus cytome (BMCyt) assay has evaluated cytotoxicity in drug abuse, there has not been an approach that takes into account this pattern of multiple drug use. Therefore, in this study, we evaluate for the first time the cytogenotoxic effects in multidrug users, and its correlation with the am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Although IDs’ direct teratogenic, genotoxic, and cytotoxic effects on human health are well-documented, emerging evidence suggests that these substances may also present significant risks to aquatic ecosystems, particularly fish populations. Research indicates that drug abusers exhibit elevated frequencies of nuclear abnormalities, including nuclear buds, binucleated cells, pyknotic nuclei, karyorrhexis, and abnormally condensed chromatin when compared to healthy controls [ 177 ]. These abnormalities may be associated with reactive oxygen species, which are produced by cytochrome P450, including P4503A and P4502B isozymes, during the metabolism of IDs.…”
Section: Bioaccumulation Of Illicit Drugs and Their Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Although IDs’ direct teratogenic, genotoxic, and cytotoxic effects on human health are well-documented, emerging evidence suggests that these substances may also present significant risks to aquatic ecosystems, particularly fish populations. Research indicates that drug abusers exhibit elevated frequencies of nuclear abnormalities, including nuclear buds, binucleated cells, pyknotic nuclei, karyorrhexis, and abnormally condensed chromatin when compared to healthy controls [ 177 ]. These abnormalities may be associated with reactive oxygen species, which are produced by cytochrome P450, including P4503A and P4502B isozymes, during the metabolism of IDs.…”
Section: Bioaccumulation Of Illicit Drugs and Their Toxicitymentioning
confidence: 99%
“…While the effects of metaphedrone were observed at relatively high concentrations (up to 100 µg/L), the findings raise concerns about the potential long-term consequences of exposure to emerging synthetic drugs. Furthermore, research on multidrug users has revealed higher frequencies of nuclear abnormalities in individuals with a history of ID abuse, indicating a correlation between drug consumption and cytogenotoxic damage [ 177 ].…”
Section: Bioaccumulation Of Illicit Drugs and Their Toxicitymentioning
confidence: 99%